Peter Pan [anglicky] - Barrie, James Matthew, 1860-1937 (Best of children´s classics, 2022)
"Children have the strangest adventures without being troubled by them." One night when Peter Pan, the mischievous little boy who can fly, is caught listening to Mrs. Mary Darling s bedtime stories, he loses his shadow while escaping. As he comes back for it, he wakes up Wendy Darling, who attaches it back to him. Peter requests Wendy to accompany him to the island of Neverland, where he lives with Tinker Bill, Lost Boys and other fairies and mermaids. As Wendy and her brothers follow Peter Pan to the island, their flight is full of adventures. But the fun has only just begun.Come! Fly with them to Neverland and join them in the adventures they are yet to encounter.